Pengaruh Variasi Bobot Gula Terhadap Kadar Vitamin C pada Puding Bunga Rosela dan Uji Hedonik - Burhan, Amelia Handayani; Putri, Salsabilla Surya; Rini, Yuli Puspito; Nurhaeni, Farisya (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2024)
Pudding is a popular snack often consumed as a dessert and enjoyed by people from various backgrounds. One of its variations is Roselle Flower Pudding, which uses roselle petals as the main ingredient. Roselle flowers are known for their high nutritional content, particularly vitamin C, which ranges from 260 to 280 mg per 100 grams. In pudding preparation, sugar is typically added to enhance flavor. However, sugar addition is suspected to affect the vitamin C content and consumer preference for the final product. This study aims to determine the effect of varying sugar weights on the vitamin C content and consumer acceptance of Roselle Flower Pudding. The research was conducted using a true experimental method, utilizing roselle flowers randomly selected from Argomulyo Subdistrict, Sedayu, Bantul. The process included identifying the roselle flower type, making pudding with sugar additions of 0, 5, 10, 15, and 20 grams, testing the vitamin C content using the iodimetric method (0.001 N titration), and conducting a preference test based on taste, aroma, color, and texture. The results showed that increasing sugar levels led to a decrease in vitamin C content: 2.52; 2.37; 2.22; 2.18; and 2.16 mg/100 grams. Conversely, consumer acceptance increased: 63.7%; 64.3%; 69.9%; 72.0%; and 76.8%. The best formulation was with 10 grams of sugar, as it maintained a relatively high vitamin C level while achieving optimal consumer preference.